(untitled) (Proceedings of International Conference on Special Education, 2017)
The working environment is an environment that will be faced by every individual after completing education or when going through adulthood. No exception also to individuals with special needs. This study investigated the challenges faced by parents with autistic kid. It also aimed to find out the implementation and perception towards transition programme. The sample involved in this case study is parents who send their child to pursue a career transition program. Data were collected through semi-structured interview with the parents. It was found that the parents are actively involved in the programme working hand in hand with the researcher. They gave full cooperation and were positive throughout the transition programme. They wished that their child can continue with the programme to help prepare him for the real working environment.